IMPACT OF DISTURBANCE FACTORS ON HIGH VALUE ENGINEERING SUPPLY CHAINS WITH ANALYTHICAL HIERARCHY PROCESS - Escobar, David (2016)
Due to globalization and market conditions, risks of disruptions are considered a “normal state” for supply chains. Therefore, managers need to start making decisions with a risk impact approach in mind. Consequently, this research demonstrated through the use AHP methodology the impact of; Firm, Supply and Environmental disturbance factors over HVE companies and relevant mitigation strategies supported with examples. Since there is not exact definition for High Value Engineering (HVE), a concept framework was developed to validate the definition suggested by Wang and Zhang, (2014): “High-value engineering is to create value for its direct and indirect beneficiaries based on integrating different functions and subjects as well as resources along the whole value creation stage, the interaction among which (including cooperation and friction) finally causes value creation” The research methodology consisted on: 1) Identification of key disturbance factors, 2) Development of AHP structure, 3) Formulation of questionnaires, 4) data collection and 5) AHP weigh computation. The highest impact disturbance factors were: “Demand-Supply Responsiveness (Supply)” had the 1st place with 25.4 % due to lack of internal communication, followed by “Interruptions in Manufacturing (Firm) with 16.7% due to poor equipment reliability, “Inaccurate Forecast” (Supply) with 12.8% and “Cost of distant Operations (Environmental) with 4.94 %. Outsourcing offshore scenario was the most vulnerable with a weigh of 49.3 %, while Outsource Nearshore had a weigh of 26% and Insource Nearshore 24.8%. 3 The following response strategies, especially flexibility, were suggested due to their multipurpose impact on results found: a) Improve the manufacturing operations reliability and flexibility by; the standardization pieces, modular sub-assemblies, implementation of redundancy concept with spare parts or extra equipment in order to adapt to demand fluctuation, improve machine reliability and reduce variation in the process, b) Improve communication and collaboration since integration help to reduce uncertainty across the supply chain.